Acute colonic pseudo-obstruction following allogeneic stem cell transplantation successfully treated by neostigmine - Yahng, Seung-Ah (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2013)
Acute colonic pseudo-obstruction (ACPO), also known as Ogilvie's syndrome, is a rare clinical syndrome of massive large bowel dilatation without mechanical obstruction, which may cause significant morbidity and mortality. Treatment focuses on decompressing a severely dilated colon. The proposed theory that this severe ileus results from an imbalance in the autonomous regulation of colonic movement supports the rationale for using neostigmine, a reversible acetylcholinesterase inhibitor, in patients who failed conservative care. Although gastrointestinal complications are frequent following allogeneic stem cell transplantation (SCT), the incidence of ACPO in a transplant setting is unknown and, if not vigilant, this adynamic ileus can be underestimated. We describe the case of a patient with myelodysplastic syndrome undergoing non-myeloablative allogeneic SCT from a partially human leukocyte antigen-mismatched sibling donor, and whose clinical course was complicated by ACPO in the early post-engraftment period. The ileus was not associated with gut graft-versus-host disease or infectious colitis. After 3 days of conservative care, intravenous neostigmine (2 mg/day) was administered for 3 consecutive days. Symptoms and radiologic findings began to improve 72 hours after the initial injection of neostigmine, and complete response without any associated complications was achieved within a week. Thus, neostigmine can be a safe medical therapy with successful outcome for patients who develop ACPO following allogeneic SCT.